FREQUENTLY ILL CHILDREN. PHYSIOTHERAPIST'S VIEW - O. M. Konova; E. G. Dmitrienko; I. V. Davydova (Педиатрическая фармакология, 2012)
The prevention of frequent respiratory infections in children is one of the urgent issues of modern pediatrics. At present the range of non-drug technologies of prevention of acute respiratory infections (ARI) in children has considerably increased due to the appearance of new effective methods of physical rehabilitation. The article gives a literary review of the main methods of drug prevention of frequent ARI in childhood applied in practical healthcare on the modern stage.